CHANGES TO THE PREFERRED MODEL OF CONSUMPTION AND THE ETHNIC IDENTITY CRISIS OF POLESHUKS IN THE EARLY TWENTIETH CENTURY - Olszewski, W. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article tells about the cultural identity crisis of Poleshuks, concentrating on the changes which emerged in preferred model of consumption after the WWI. The author, inspired by the materials collected in Polesia by Józef Obrębski in the first half of Twentieth century, analyzes the causes and consequences of those significant changes.